(3GdaUjM aj GddZIs - (3CMeO Hf jMji Hf RjO Hf SjGQ GdTjHGfqj HGdhdGA, CHh GdYHGS, GdeYQha HKYdH,J (B291 (3g` s ((3GHQGgje Hf eMeO GdCfOdSi s)
(3ChdgG (B:s
(3Chd GdehLhO efgG , bhdg (B: (3HGH aYdJ HZjQ Cda , Jbhd (B: (3TedJ GdQjM ef GdTeGd hLfHJ ef GdLfhH hOHQJ ef GdOHhQ s
(3BNQgG (B:s
(3hbGd GHf GdCYQGHi hjbGd dLOd HjVI GdEfSGf GdUaf hjbGd dg ef PhGJ GdNa Je GdcJGH hGdMeO ddg s
(3GdfSNI ebGHdIs
(3HgG fXGe GdJYbjHIs
(3bWYI ef BNQgs
(3fSNI QGHYI fbdJ ef fSNI SbjeI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GddZIs